Estudio de la formación de fisuras de desecación por medio de fractales (2020)
In this paper were analyzed the desiccation cracks produced in a clay soil using fractal mathematic. This soil, composed of Kaolin and Bentonite, was studied in four different sizes of mold, with the aim to know how is the influence of this parameter in the formation of the cracks, having as a result, a numerical characterization of a chaotic phenomenon, which is relevant in clay soil in dry seasons.Subsequently, this result could be associated with the properties and parameters of the soil, thus knowing the cracks response to environmental factors, the mineralogy composition of the soil and other factors. Conducting a fractal analysis through box counting method, it is found the fractal dimension of a mold in a specific time, which is going to be related not only to the others molds, but also to the others monitoring times, with the intention to discover the relations that bind together the time, the size and the fractal dimension. The main connections that were identified are: the ratio among the fractal dimension and the size of the mold is inversely proportional, and the ratio among the fractal dimension and the cracking time is directly proportional.